2006
DOI: 10.1097/01.pas.0000208898.38730.36
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactivity for Sex Steroid Hormone Receptors in Pulmonary Hamartomas

Abstract: Sex steroid hormone [ie, estrogen (ER), progesterone (PgR), and androgen (AR)] receptors have been identified previously in normal salivary glands and, more variably, in salivary gland and salivary gland-type tumors. No data are available, however, on their expression in pulmonary hamartoma, a benign biphasic tumor consisting of reactive epithelial cells and neoplastic fibromyxoid stroma, cartilage and fat, which shares some morphologic, immunophenotypic, and genotypic features to pleomorphic adenoma of major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 68 publications
0
8
1
Order By: Relevance
“…Interestingly, chondroid hamartomas contain stromal cells immunohistochemically expressing ER, PgR, and smooth muscle markers; however, the stromal cells differed from the spindle cells of the present case in that the stromal cells were associated with fibromyxoid substances and were also positive for S100 and glial fibrillary acid protein. Among other rare cases of pulmonary hamartoma, a recent case report described a fibroleiomyomatous hamartoma containing smooth muscle marker‐positive spindle cells that were also positive for PgR but not ER.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…Interestingly, chondroid hamartomas contain stromal cells immunohistochemically expressing ER, PgR, and smooth muscle markers; however, the stromal cells differed from the spindle cells of the present case in that the stromal cells were associated with fibromyxoid substances and were also positive for S100 and glial fibrillary acid protein. Among other rare cases of pulmonary hamartoma, a recent case report described a fibroleiomyomatous hamartoma containing smooth muscle marker‐positive spindle cells that were also positive for PgR but not ER.…”
Section: Discussioncontrasting
confidence: 68%
“…Additionally, another case of fibroleiomyomatous hamartoma contained stromal cells that were negative for both receptors. Sex steroid hormone receptor‐positive stromal cells in chondroid hamartomas are thought to be influenced by the patients' sex and to be related to the development and growth of the mass; this may be true in the present case. During a 1‐year follow up, the patient's acquired lung lesion enlarged, with formation of numerous multiloculated spaces.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The expression of sex hormone receptors in some tumors suggests a role for these receptors in tumor pathogenesis and therapy. Previous reports indicated the possible expression of estrogen receptor (ER) in salivary gland tumors and suggested that sex hormones could have a role in the management of salivary gland tumors because there is a well-established similarity of basic acinar and ductal structures between breast tissue and salivary glands, but the results were inconclusive or conflicting due to the small number of cases and variant assay technique 4 - 8 . The sex hormone estrogen plays an important role in controlling the expression of genes involved in a wide variety of biological and neoplastic processes.…”
mentioning
confidence: 99%